Cuscuta chinensis Antidepressant-Like Effect, the Role of 5-HT and the Impact on Behavioral Response in Mice - Maryam Hamzeloo-Moghadam*; Leila Ara; Fatemeh Jafari; Roshanak Mokaberinejad (Iranian Society of Pharmacognosy, 2022)
Background and objectives: Depression is a chronic mental disorder that influences people's lives and functionality.  The available medications do not give full guaranty of effectiveness and are not devoid of unwanted side effects.  Cuscuta chinensis has been recommended for the treatment of depression in traditional medicine. In this study, the antidepressant-like activity of C. chinensis has been evaluated by using forced swimming test (FST) in mice. Methods: Cuscuta chinensis extract was provided by boiling in water. The antidepressant effect was evaluated by forced swimming test (FST) in mice with daily gavage of 270, 360 and 430 mg/kg of the treatments for four weeks. The immobility time and behavioral activity and also the blood levels of 5-HT and norepinephrine were measured. Results: The FST confirmed antidepressant effect of the extract with decreased time of immobility and increased swimming time alongside increase in serum 5-HT in all groups (p<0.01compared to the control) except for the extract at the dose of 270 mg/kg (MA270).  This effect was not statistically significant with fluoxetine group. Conclusion: Cuscuta chinensis demonstrated antidepressant effects in mice model which is a confirmation for its traditional use in depression.